ANALISIS WAKTU DAN BIAYA TENAGA KERJA LANGSUNG PROYEK MENGGUNAKAN CRITICAL CHAIN PROJECT MANAGEMENT (STUDI KASUS: PROYEK PEMBANGUNAN APARTEMEN DELFT & KANTO MAKASSAR) - Maydeline Caroline Faihu; Stevy Thioritz; Mursalim (Jurnal Media Teknik Sipil, 2023)
Planning in a project is essential because it functions as a supervisory tool or a guideline needed in controlling activities so that the project can continue to run within the specified time, cost and quality limits. However, it is undeniable that various conditions often occur that can cause project to experience failures, such as delays and cost overruns. To avoid these things, project resources must be managed effectively and efficiently in order for the project to not experience failures. This research aims to determine the time and direct labor cost of the project obtained from alternative project scheduling using the Critical Chain Project Management. CCPM replaces activity’s safety time by incorporating buffers into the project schedule due to limited resources and project uncertainty. There are 3 types of buffers in the CCPM method, which is project buffers, feeding buffers and resource buffers. The results of this research showed that Critical Chain Project Management resulted a total duration of 209 days and obtained direct labor cost of Rp1.779.736.000,00 (one billion seven hundred seventy-nine million seven hundred and thirty-six thousand rupiah) if it was assumed that the entire buffer time was 100% used.